TRANSFORMATIONAL LEADERSHIP MANAGEMENT IN IMPROVING THE PERFORMANCE OF EDUCATORS AND EDUCATIONAL PERSONNEL - Mashudi Harianto (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
This study aims to determine the effect of transformational leadership management on the performance of educators and education personnel. many things are related in order to support the success of an Islamic educational institution one of which concerns the style displayed by the figure of the leader or the pattern of behavior that he displays in leading. In general leadership style there are two leadership styles namely task oriented style (task oriented), and member oriented style (employee-oriented). In subsequent developments along with social changes the model and style of leadership underwent a change in the style of transactional leadership, transformational leadership, and visual leadership. This research uses a descriptive quantitative approach. Data from this study were obtained from the school principal, board of teachers and other school staff at SMP Muhammadiyah 2 Taman. Data collected by observation, interview and documentation. The data analysis technique used is descriptive - qualitative. The results of the study indicate that transformational leadership management is able to improve the quality of the performance of educators and education personnel in SMP Muhammadiyah 2 Taman.